Finite particle size effects on dynamic and structural properties of deep eutectic solvents based on caprylic acid: From a perspective of molecular dynamics simulation - Samaneh Barani Pour; Mitra Dabbagh Hosseini pour; Jaber Jahanbin Sardroodi (Results in Engineering)
The increasing interest of the pharmaceutical industry in deep eutectic solvents (DESs) has heightened the demand for predicting their bulk properties and advancing the development of these eco-friendly solvents. Meanwhile, caprylic acid-based DESs have gained significant attention due to their unique physicochemical properties and potential applications in various fields. However, the influence of finite particle size on the structural properties and bulk property predictions of these DESs remains largely unexplored. In addition, the investigation focuses on the influence of nanoscale confinement on the organization and interactions of DES components. In this respect, MD simulations were used to systematically investigate the influence of finite-size effects on essential properties, including hydrogen bonding networks, diffusivity and distribution of species around each other in the binary mixtures. Our findings reveal that system size markedly affects the local structuring and dynamic behavior of DES components, leading to deviations from the prediction of the bulk properties. Velocity autocorrelation functions (VACFs), vector reorientation dynamics (VRD) of DES species, and other results provide valuable insights into the limitations and potential pitfalls of using finite-size systems for the prediction of the properties of DESs. The results indicate that systems with 1000 particles provide satisfactory predictions of thermophysical properties compared to other system sizes. This is because the self-diffusion coefficient from molecular dynamics simulations (DMD) values approach the self-diffusion coefficient values observed in the thermodynamic limit. Notably, the density profile results reveal that confinement within nanotubes significantly influences the structural properties of eutectic solvents. Therefore, this study provides a fundamental understanding of the confined behavior of DESs, which is crucial for their application in emerging nanotechnologies.